The Reality Of Applying Management Engineering In College Of Education For Pure Sciences / Ibn Al-Haitham - Omar Azhar Ali (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of the research is to identify the reality of applying management engineering at Ibn al-Haitham College of Education at Baghdad University, as well as the significant differences from the perspective of the targeted sample according to gender and years of service. The researcher addressed the problem of the search as well as its importance. The researcher adopted the analytical descriptive approach by identifying the research community which consists of 55 members with senior administrative positions from Dean to an manager unit official at the college for the academic year (2019-2020). The research sample consists of 39 membrs that cover 71% of the community. The researcher has used a special search technique for the (questionnaire) consists of four fields to ensure its reliability. The theoretical aspect and previous studies on the subject were presented, besides, the researcher <a href="https://www.reverso.net/translationresults.aspx?lang=EN&sourcetext=حيث%20تم%20عرض%20الجانب%20النظري%20والدراسات%20السابقة%20المتعلقة%20بالموضوع%20،قام%20الباحث%20بعرض%20وتحليل%20النتائج%20ومناقشتها%20،%20ثم%20خرج%20الباحث%20بنتائج%20أهمها%20ان%20واقع%20تطبيق%20الهندسة%20الادارية%20في%20الكلية%20كان%20بمستوى%20متوسط%20واقرب%20الى%20الضعيف%20،%20فيما%20لم%20تظهر%20فروق%20ذات%20دلالة%20في%20متغير%20الخدمة%20،%20بينما%20ظهرت%20فروق%20في%20متغير%20الجنس%20ولصالح%20الاناث.%20ثم%20وضع%20الباحث%20عددا%20من%20الاستنتاجات%20والتوصيات%20والمقترحات%20الخاصة%20بالبحث&action_form=translate&direction_translation=ara-eng-5">analyzed, discussed then submitted the results, the most important of which is that the application of management engineering in the college was of a moderate and near-weak level, while no significant differences appeared in the service variable. Differences in gender and female-favor appeared. The researcher then drew up several conclusions, recommendations, and proposals.